Life traces of the Georgia coast : revealing the unseen lives of plants and animals - Martin, Anthony J., 1960- (Life of the past., 2013)
Have you ever wondered what left behind those prints and tracks on the seashore, or what made those marks or dug those holes in the dunes? Life Traces of the Georgia Coast is an up-close look at these traces of life and the animals and plants that made them. It tells about how the tracemakers lived and how they interacted with their environments. This is a book about ichnology (the study of such traces) and a wonderful way to learn about the behavior of organisms, living and long extinct.